Influencing factors of parenting stress in parents of children with autism spectrum disorder - YIN Peipei, XING Yipei, JI Yue, ZENG Shuting, LIANG Fengjing, CEN Chaoqun (Xin yixue)
Objective To investigate the factors influencing parenting stress among parents of children with autism spectrum disorder （ASD）， aiming to provide personalized guidance and support for parental care in family interventions. Methods A total of 302 families with young children with ASD who received inpatient interventions at the Child Developmental and Behavioral Center of the Third Affiliated Hospital of Sun Yat-sen University from May 2022 to February 2024 and their parents were recruited to complete the questionnaires， which included Socioeconomic Status Scale （SES）， Parenting Stress Index-Short Form （PSI-SF）， Social Responsiveness Scale-Second Edition （SRS-2） and Adaptive Behavior Assessment System-Second Edition （ABAS-Ⅱ） of the children. Subsequently， relevant data were analyzed. Results There were no statistical differences in parenting stress among parents based on the gender of child， the age of child， parenting style， gender of the primary intervention parent， family annual income， father’s education， and mother’s occupation （all P > 0.05）. However， there were statistical differences in parenting stress among parents in terms of the number of children in the family， mother’s education， and father’s occupation （all P < 0.05）. The scores of PSI-SF were negatively correlated with the comprehensive scores of ABAS-Ⅱ for young children with ASD （P < 0.01）， whereas were positively correlated with the total scores and the score of each dimension of SRS-2 （P < 0.01）. The number of children in the family and ABAS-Ⅱ comprehensive score could not predict parenting stress， while mother’s education， father’s occupation and SRS-2 total score could predict parenting stress， explaining 26.8% of the variance in parenting stress. The effect size of SRS-2 total score was 0.17， contributing the most to regression equation. The main predictor of SRS was the restricted and repetitive behavior dimension （B = 0.709， β = 0.213， P < 0.05）， explaining 21.8% of the variance in parenting stress. Conclusions The more severe the social impairment in the young children with ASD， particularly in terms of restricted interests and repetitive behaviors， the greater the parenting stress. This suggests that in promoting family interventions guided by parents， we should not only focus on alleviating core social communication impairments， but also emphasize parents’ understanding and intervention in children’s restricted interests and repetitive behaviors.